Towards Effective Implementation of E-Governance In Rural Development (Trinity Journal of Management, IT & Media (TJMITM), 2021)
In recent decades the nation of e-Governance has received special action in the field of rural development and its successful implementation of various welfare taken for the development of rural areas. The basic objectives of e-Governance programs are to provide government services to every individual  twenty four hours.E-Governance is the application of information and communication technologies (ICTs) to improve the activities of government agencies. today, across the world governments are using several e communication strategies to effectively administer the public and private activities of which India is one of them. However, the e-readiness index of India is found to be low in comparison to other countries. In fact there are various challenges for the implementation of e-government in India. These challenges are low literacy, low per capita income, lack of legal and technical infrastructure, and limited financial resource amongst others. The purpose of this paper is to examine the  challenges encountered in e-governance in Asian nation  and to  spotlight the different gaps that hinder the implementation there of thereafter, with the support of secondary data and by reviewing the existing literature, the paper will identify the various strategies that can be adopted for having an effective e- governance framework in India.
Keywords: ICT; E-Governance and E- Governance Strategy; Rural Development; E-Government